Inorganic Carbon Transport and Dynamics in the Florida Straits. Issue 10 (6th October 2022) - Xu, Yuan‐Yuan; Wanninkhof, Rik; Osborne, Emily; Baringer, Molly; Barbero, Leticia; Cai, Wei‐Jun; Hooper, James
Abstract: Ocean heat and carbon are transported through the Florida Straits, contributing to the Atlantic Meridional Overturning Circulation, and playing an important role in climate. Insufficient observations of carbonate chemistry within the Florida Straits have limited our understanding of ocean acidification within this region. To examine carbonate chemistry and carbon transport dynamics within this region, we developed an algorithm to estimate dissolved inorganic carbon (DIC) using more routinely measured input parameters (temperature, salinity, and dissolved oxygen [DO]) and the corresponding sampling date, depth, and longitude. The developed DIC algorithm output demonstrates good agreement with limited existing in situ observations. By applying this algorithm, we developed a seasonally resolved time series of DIC spanning from 2002 to 2018 for the Florida Straits at 27°N. This time series suggests that short‐term variations in surface water DO and DIC were strongly influenced by the Florida Current transport. The long‐term increase in DIC was mainly caused by anthropogenic carbon accumulation and DO decrease. The highest increasing rate in DIC was found in North Atlantic Central Water where DO decrease was fastest while the decreasing rate in pH was highest in Antarctic Intermediate Water (AAIW) because of the lower buffer capacity of this water mass. The long‐term pH decrease, especially in AAIW, can impact the health of deep corals in the Florida Straits. Quantifying carbon transport between the coast of Florida and the Bahamas is important to understanding the carbonate chemistry dynamics and the long‐term acidification of this important region. Plain Language Summary: A large amount of ocean heat and carbon is transported northward through the Florida Straits, the upper limb of the Atlantic Meridional Circulation, and plays a role in ocean carbonate chemistry along the U.S. east coast. Our understanding of carbon transport and ocean acidification in the Florida Straits is limited by insufficient carbonate chemistry data within this region. To address this issue, we developed an algorithm based on high‐quality data from carbonate chemistry‐focused research cruises. Then we applied this algorithm to seasonally resolved hydrographic time‐series data from 2002 to 2018 to generate the carbonate chemistry datasets for the study region. We found that short‐term variation in surface water dissolved oxygen was strongly correlated with volume transport. During the past two decades, dissolved oxygen showed a significant decreasing trend, and dissolved inorganic carbon showed a significant increasing trend. In addition, the increasing rate of dissolved inorganic carbon was highest in North Atlantic Central Water where the decreasing rate in dissolved oxygen was greatest. Furthermore, the long‐term declines in pH and aragonite saturation state have the potential to threaten the health of corals living in the Florida Straits. Key Points: Short‐term variations in surface water oxygen and dissolved inorganic carbon concentrations are strongly influenced by the Florida Current transport Anthropogenic carbon accumulation and dissolved oxygen decrease are two main factors that lead to the long‐term increase in dissolved inorganic carbon of the Florida Straits The highest long‐term rate of increase in dissolved inorganic carbon of North Atlantic Central Water is likely due to the highest rate of increase in respiration